Partial Virological Response after 2 Years of Entecavir Therapy Increases the Risk of Hepatocellular Carcinoma in Patients with Hepatitis B Virus-Associated Cirrhosis - Shin, Seung Kak; Yim, Hyung Joon; Kim, Jeong Han; Lee, Chan Uk; Yeon, Jong Eun; Suh, Sang Jun; Jung, Young Kul; Kim, Yun Soo; Kim, Ju Hyun; Kwon, Oh Sang (Gut and liver, 2021)
: The clinical significance of partial virological response (PVR) in patients undergoing antiviral therapy is not well known. This study investigated whether PVR after 2 years of entecavir (ETV) therapy is associated with hepatocellular carcinoma (HCC) development in cirrhotic patients. A total of 472 naïve patients with hepatitis B virus (HBV)-associated cirrhosis who were treated with ETV for at least 2 years were retrospectively enrolled. Clinical characteristics, laboratory data, PVR, and noninvasive fibrosis markers (aspartate aminotransferase to platelet ratio and FIB-4 index) at 2 years after ETV commencement were analyzed for HCC risk. After excluding those who developed HCC within 2 years of ETV therapy, 359 patients (mean age, 51±10 years; male 64.3%) were examined. During a median follow-up of 82 months, 80 patients developed HCC. In the univariate analysis, older age (hazard ratio [HR], 1.056; p<0.001), PVR (HR, 2.536; p=0.002), higher aspartate aminotransferase (HR, 1.018; p=0.005), lower albumin level (HR, 0.463; p<0.001), lower platelet count (HR, 0.993; p=0.01), and higher FIB-4 index (HR, 1.141; p<0.001) at 2 years after ETV commencement were risk factors for HCC. In the multivariate analysis, older age (HR, 1.046; 95% confidence interval [CI], 1.022 to 1.072; p<0.001), PVR (HR, 2.358; 95% CI, 1.310 to 4.245; p=0.004), and higher FIB-4 index (HR, 1.103; 95% CI, 1.035 to 1.177; p=0.003) were independent risk factors. PVR and higher FIB-4 index after 2 years of ETV therapy were independent risk factors for HCC. Therefore, efforts to accomplish a complete virological response and reduce the FIB-4 index should be made.